Insight on intrusion behavior of compacted bentonite with accessory-mineral ring: a modelling approach - Xu, Libo; Ye, Junneng; Yao, Yanming (Frontiers in Materials, 2025)
Investigating the intrusion behavior of buffer/backfill materials is a critical aspect in the design of high-level radioactive waste (HLW) disposal repositories. This study proposes an intrusion model that accounts for the influence of the accessory-mineral ring and refines it by incorporating the specimen saturation process. The results show that the model demonstrated good agreement with the measured values after 30 days, but less accurate prior to this time. After incorporating a correction for the specimen’s saturation process, the model could well predict the measured values throughout the whole intrusion process. Additionally, the study suggests that predictions under parallel montmorillonite plates may be lower compared to non-parallel plates. The accessory-mineral ring significantly inhibits bentonite intrusion, and its restraining effect increases with the ring’s width. Compared to the smooth acrylic fissures, the irregular fractures in actual disposal repositories further limit bentonite intrusion. Fracture water seepage restricts bentonite intrusion in the upper part of the specimen while promoting it in the lower part, and also enhances the inhibiting effect of the accessory-mineral ring. The extent of this effect depends on the water flow velocity. Furthermore, increasing temperature promotes bentonite intrusion.